Assessing the undrained strength cross-anisotropy of three tailings types. Issue 1 (11th March 2022) - Reid, D.; Fanni, R.; Fourie, A.
Abstract : The cross-anisotropic nature of soil strength has been studied and documented for decades, including the increased propensity for cross-anisotropy in layered materials. However, current engineering practice for tailings storage facilities (TSFs) does not appear to generally include cross-anisotropy considerations in the development of shear strengths. This is despite the very commonly seen layering profile in subaerially deposited tailings. To provide additional data to highlight the strength cross-anisotropy of tailings, high-quality block samples from three TSFs were obtained and trimmed to enable hollow cylinder torsional shear tests to be sheared at principal stress angles of 0 and 45° during undrained shearing. The consolidation procedures were carried out such that the drained rotation of principal stress angle that would precede potential undrained shear events for below-slope tailings was reasonably simulated. The results indicated the significant effects of cross-anisotropy on the undrained strength, instability stress ratio, contractive tendency and brittleness of each of the three tailings types. The magnitude of cross-anisotropy effects seen was generally consistent with previous published data on sands.